2023
DOI: 10.1108/jcp-07-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Introduction “stalking: what do we know about working with people who stalk and where do we go?”

Abstract: Purpose There is an absence of qualitative research with individuals who have stalked. This special issue of articles draws on one study, rich with the meaning-making of experts by experience. That is, people who have stalked, been convicted and detained in UK prisons. The purpose of this issue is to provide forensic practitioners with an overview of current considerations for intervening with individuals who stalk. It does this by drawing together empirically derived interpreted experiences of men who stalk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…Interestingly, a diagnosis of psychopathy was not found in any of the presented cases, even though all culminated in extreme violence and motivations for gaining control and dominance was noted in some perpetrators (Storey et al, 2009). Finally, while we found that personality disorders were rare, personality disorder traits were noted which supports wider literature findings (Wheatley, 2023 The exploratory case study analysis revealed common themes across the cases:…”
Section: Overview Of the Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Interestingly, a diagnosis of psychopathy was not found in any of the presented cases, even though all culminated in extreme violence and motivations for gaining control and dominance was noted in some perpetrators (Storey et al, 2009). Finally, while we found that personality disorders were rare, personality disorder traits were noted which supports wider literature findings (Wheatley, 2023 The exploratory case study analysis revealed common themes across the cases:…”
Section: Overview Of the Resultssupporting
confidence: 78%
“…With regards to risk, each case had at least one risk factor from each risk category that is, the red flags, general risk, and risk specific to the stalking type. Overall, there was a low prevalence of mental illness and autism spectrum disorder (ASD) which is in line with wider research suggesting that majority of those who stalk do not suffer from serious mental illness or ASD, although those with ASD traits may present in cases when a person aims to establish an intimate relationship in the context of inadequate social functioning (Mcguire & Wraith, 2000;Wheatley, 2023). Although Wheatley (2023) notes that ASD traits would most commonly be found in incompetent suitors, in our sample this was the case for the resentful stalker.…”
Section: Overview Of the Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Thus, while there is potential for ICTs to be used positively in intimate relationships (e.g., keeping in contact when apart), ICT may also be used negatively (e.g., invading privacy, covert monitoring) (Wright, 2015). Both offline and cyber IPA includes behaviors such as threats, insults, humiliation, excessive monitoring, tracking, stalking and omnipresence intended to control, distress, or isolate a partner (Borrajo et al, 2015;Creamer & Hand, 2022;Sheridan, 2023;Wheatley, 2023;Woodlock, 2017). Yet cyber IPA and reallife IPA are distinguishable by a number of features.…”
Section: Introductionmentioning
confidence: 99%